1986
DOI: 10.1002/1097-0142(19861001)58:7<1400::aid-cncr2820580703>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Congenital fibrosarcoma. Preoperative chemotherapy and conservative surgery

Abstract: Three cases of congenital fibrosarcoma are reported. The use of preoperative chemotherapy, a VAC regimen, allowed conservative surgery in two of them. The three children are well, with no evidence of disease and without sequelae after completion of postoperative chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…Ninane et al9 reported the successful use of preoperative chemotherapy enabling limb sparing procedures for complete resection. Grier et al 6 reported (in 1984) on 2 patients treated for unresectable retroperitoneal fibrosarcoma with doxorubicin, vincristine, and cyclophosphamide, who were disease free at 4 years.…”
mentioning
confidence: 99%
“…Ninane et al9 reported the successful use of preoperative chemotherapy enabling limb sparing procedures for complete resection. Grier et al 6 reported (in 1984) on 2 patients treated for unresectable retroperitoneal fibrosarcoma with doxorubicin, vincristine, and cyclophosphamide, who were disease free at 4 years.…”
mentioning
confidence: 99%
“…Results of preoperative and/or postoperative CT in congenital ® brosarcoma were reported in several series [13,14] and proved to be an ef® cient treatment. The aim is to shrink the tumor and avoid a mutilating procedure or to treat minimal residual disease after conservative surgery, as we reported [15].…”
Section: Discussionmentioning
confidence: 97%
“…This tumour should be initially treated by surgery alone with local excision of the lesion without impairing functionality. Occasionally adjuvant chemotherapy is advisable [9,11]. The risk of recurrence in further pregnancies is unknown.…”
Section: Discussionmentioning
confidence: 99%